'Formalizing' Land Tenure in First Nations: Evaluating the Case for Reserve Tenure Reform - Baxter, Jamie; Trebilcock, Michael (Indigenous Law Journal, 2009)
Jamie, Baxter is a JD Candidate, Faculty of Law, University of Toronto. A proposal is currently being drafted by the First Nations Tax Commission to create a national First Nations Land Title System (FNLTS) for reserve lands in Canada. This paper examines the implications of the FNLTS proposal for some economic development outcomes across diverse First Nations communities. The authors aim to situate the theory underlying a FNLTS within recent international development scholarship on land tenure formalization, asking whether and under what conditions net benefits from tenure reform are likely to be realized. Their evaluation begins with a brief overview of the history of reserve land tenure in Canada, followed by a survey of the tenure regimes currently available to First Nations, thus providing context for suggested reforms. The second half of the paper draws on the experiences of Indigenous communities with tenure formalization in the United States, New Zealand, Australia, and South Africa. Overall, the authors conclude that the predicted economic outcomes of a FNLTS will depend heavily on historical, political, social and geographic factors unique to each community. First Nations will likely need to consider creative strategies for tenure reform tailored to their particular circumstances and traditions in order to meet economic development goals.